STUDENT EMPATHY TRANSFORMATION: AN EXPERIENTIAL LEARNING APPROACH WITH SPECIAL NEEDS CHILDREN: TRANSFORMASI EMPATI MAHASISWA: PENDEKATAN PEMBELAJARAN BERBASIS PENGALAMAN PADA ANAK DENGAN KEBUTUHAN KHUSUS - Sri Hartini Mardi Asih; Siti Lestari; Ratnasari Ratnasari; Dwi Fitriyanti; Dhanang Efendi (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Caring for children with special needs requires a holistic approach. However, research on culturally suitable play interventions in developing countries remains scarce. YPAC Semarang faces challenges in stimulating motoric and social skills due to a high caregiver-to-child ratio. Objective: This program aimed to assist children through play therapy and creative health education while transforming nursing students' sympathy into empathy through direct experience. Method: Implemented September 26th, 2025, at YPAC Semarang, this study utilized a convergent mixed-methods approach, combining quantitative (pre-post structured observations) and qualitative (students’ reflective journals) data, analyzed separately and then brought together for overall interpretation, involving 50 students and 50 children (1:1 ratio). Activities included modified gymnastics, traditional song-guided hygiene lessons, and expressive handprint activities. Data were collected via structured observation sheets and students' reflective journals, then analyzed using descriptive statistics and thematic analysis. This aligns with experiential learning philosophy, which utilizes direct experience as the foundation for learning through the cycle of concrete experience and reflective observation. Results: Children showed high engagement (85-100% attendance). Post-intervention, 75% of children mastered handwashing, and 70% demonstrated correct toothbrushing. Thematic analysis revealed four themes: transformation of sympathy to empathy (reported by 90%), discovery of patience, awareness of uniqueness, and professional commitment. Conclusion: This program successfully stimulated development in children and effectively fostered clinical empathy in nursing students.